Chronic Bacterial Prostatitis: Current Microbiological Spectrum and Sensitivity Pattern - Shakil, 1Mohsin; Khan, 2Mumtaz Ahmad (International Journal of Pathology, 2018)
Introduction: The incidence of Prostatitis is increasing considerably worldwide. Clinical diagnosis of Prostatitis is mostly based on signs and symptoms. Laboratory diagnosis relay on microscopy culture of expressed prostatic secretion (EPS). Studies regarding bacterial prostatitis are limited in Pakistan. This study determines microbiological profiles and resistance patterns of infecting organisms in prostatitis in a general hospital.Objective: To determine the bacterial agents and their antibiotic sensitivity pattern from EPS samples of patients presenting symptoms of chronic prostatitis.Materials and Methods: The cross-sectional study was carried out in the Microbiology department, Abbas Institute of Medical Sciences, Muzaffarabad from January 2015 to March 2016. A total of 298 samples of prostatic secretions from patients suspected with prostatitis were cultured by a semi-quantitative method. The isolated bacteria were identified by colony morphology, Gram’s staining, motility and biochemical tests. Antibiotic sensitivity was done according to the CLSI guidelines 2015 by disc diffusion method. WHONET Version 5.6 was used for compilation and calculation of data.Results: The EPS cultures from patients with chronic Prostatitis, showed n=177/298 (59.4%) culture positivity. Out of all specimens, 108(36.2%) samples yielded no growth and 13 (4.36%) yielded normal meatal flora (S. epidermidis). 177 (59.4%) samples yielded the significant growth. The frequencies of Gram-positive and Gram negative bacteria were 54.8 %( n=97 and 45.2% (n=80), respectively. Methicillin sensitive Staph aureus (MSSA) and Methicillin-resistant Staph aureus (MRSA) were the two leading Gram positive isolates while E coli, Klebsiella and Acinetobacter species were the three leading Gram negative isolates.Conclusion: In conclusion, this study showed a different microbiological profile which will help the physicians in selection of empirical therapy for CBP.